Validation of the Spectrophotometry method on the concetration assessment of Enrofloxacine as the Animal Drug - Ambarwati .; Novida Ariyani; Maria Fatima Palupi (Jurnal Sain Veteriner, 2013)
Abstract Validation for analysis of enrofloxacin injection method using spectrophotometry has been conducted. Enrofloksasin in a solution of NaOH (sodium hydroxide) 0.1 N, measured at the maximum wavelength (ë) 271 nm.The parameters of validation that were carried out are precision, accuracy, linearity, limit of detection and limit of quantitation. Precision showed good results with coefficien variation (CV) results smaller than that of CV Horwitz. Accuracy parameters calculated by the method of analysis to determine levels of analyte in a known active ingredient purity and yielded 0.449%. Linearity parameters showed good results with r = 0.9996. Limit of detection value was obtained for 0.757 μg / mL and limit of quantification of 2.522 μg / mL. The results of validation test of enrofloxacin injection analysis using spectrophotometric method can be used as a good method to provide a valid test of quality assurance veterinary drugs.